Busytown boat race - Scarry, Richard (New York : Aladdin Paperbacks, 1997)
Huckle and Lowly are all set for the busytown boat race, but they have to works hard to steer clear of Mr. Frumble.
Adapted from the animated television series: The Busy World of Richard Scarry
Keywords: Racing-Fiction; Boats and boating-Fiction; Animals-Fiction